Gestational age-specific normative values and determinants of serum progesterone through the first trimester of pregnancy - Ku, Chee Wai (2021)
Progesterone is a steroid hormone that is critical for implantation and maintenance of pregnancy, and low levels are associated with higher miscarriage risk. However, little is known about its trajectory during early pregnancy. We sought to determine the gestational age-specific normative values of serum progesterone on a week-by-week basis, and its associated maternal and fetal factors, during the first trimester of a viable low-risk pregnancy. A cross-sectional study was conducted at KK Women's and Children's Hospital from 2013 to 2018. 590 women with a single viable intrauterine low-risk pregnancy, between gestational weeks 5 and 12, were recruited. Serum progesterone showed an increasing trend during the first trimester, with a transient decline between gestational weeks 6-8, corresponding to the luteal-placental shift. Lowest levels were seen at week 7. Maternal age, BMI, parity, gestational age and outcome of pregnancy at 16 weeks' gestation were found to be associated with progesterone levels. Normative values of serum progesterone for low-risk pregnancies would form the basis for future work on pathological levels of serum progesterone that may increase risk of miscarriage. Larger studies are required to validate these normative values, and personalize them to account for maternal age, BMI, parity and gestational age.